Democratic Republic of Sao Tome And Principe : Request for Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for the Democratic Republic of Sao Tome And Principe. (IMF Staff Country Reports; Country Report, 2020)
The COVID-19 pandemic is taking a heavy toll on Sao Tome and Principe. Tourist arrivals came to an abrupt halt in mid-March, externally financed projects are being delayed, and international supply-chains are disrupted. The challenging circumstances are further affected by the fragility of the economy and a weak health care system.